Improving donor support for urban poverty reduction - Nicola Banks (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The growing urbanization of poverty poses a significant challenge to governments and donors alike, particularly in Asia, which houses 60 per cent of the world's slum dwellers. Donors have been slow to respond to the urban challenge, however, both in their funding patterns and their priorities. There remains, therefore, significant scope for tangible benefits for the urban poor through greater formal and informal recognition, and in the process, through improved access to services and infrastructure, and improved health outcomes. Key to meeting these goals, however, is overcoming the social and political exclusion of the urban poor, which has so far been a key obstacle to donor involvement in the urban sector. Where national governments in developing countries remain reluctant to recognize the urban poor, donors must seek new funding mechanisms for urban poverty reduction, as discussed here. Where there have been successes in improved service delivery for the urban poor, it has been generated by collective mobilization of low-income households themselves, as active agents, allowing them to press their demands for greater legitimacy and recognition in rules and regulations, entitlements, and service provision. New forms of partnership will be required. For greater progress in urban poverty reduction to be made, however, the ability to support new forms of decentralized aid must be accompanied by a greater commitment from donors to urban poverty within their priorities and funding patterns.
Keywords: F35; I32; O19; R51; 330; urban poverty; foreign aid; Bangladesh; South Asia; Städtische Armut; Armutspolitik; Entwicklungshilfe; Bangladesch; Südasien